Sistem Informasi Berbasis Web Untuk Pengelolaan Pengaduan Pemeliharaan Pohon Di Dinas Perkim Kota Tanjungpinang - Vadilla, Qorry Endria; Rahayu, Vita; Muffarid, M. Fauzi (Jurnal Bangkit Indonesia, 2025)
The decline in the quality and maintenance of trees in urban areas, especially along roadsides, can pose risks such as tree falls and environmental damage. In Tanjungpinang City, there is no fast and integrated reporting channel to address these issues. This study aims to design and develop a web-based information system that enables the public to easily report tree conditions while increasing public participation in environmental conservation. The research methods include field observations, interviews with the Tanjungpinang City Perkim Office, literature review, and software development using the Agile method through planning, design, development, testing, implementation, and review stages. The results show that the developed web-based complaint system facilitates real-time reporting, increases transparency in handling, and speeds up follow-up processes compared to manual methods. The system is expected to be further enhanced with real-time report status monitoring features for greater effectiveness.